Comic Timbul Cerdisbusi Assisted by Virtual Class to Improve Student Learning Outcomes in Elementary Schools - Astari, Ayu Chandra (Jurnal Didaktika Pendidikan Dasar, 2021)
The purpose of the research is to solve the problem of comic arising Cerdisbusi that occurred in class VI learning SDN Oro-Oro Ombo 02 Batu in the study of theme 2 on KD IPS and Bahasa Indonesia. KD requires students to understand the material and present the visual, written, and verbal reports. Teachers improve their learning using Cyber class assisted CerDisBuSi The research method used is class action research (PTK) with 2 cycles that each cycle consists of two meetings. From the results of reflections on cycle II, students who meet the KKM of 30 students (94%) Students in the aspect of understanding the material with an average of 86.67 and as many as 29 students (90%) In the skill aspect of presenting the report with an average value of 85.00. Each aspect assessed in Cycle 2 increases from the I cycle results. It can be concluded that comics embossed in cyber-class assisted Certain can improve the learning outcomes of elementary school students.